High-Pressure Hydrogenation: A Path to Efficient Methane Production from CO2 - Maitê L. Gothe; Adolfo L. Figueredo; Laís R. Borges; Ruben Ramos; Andreia F. Peixoto; Pedro Vidinha (Methane, 2024)
Methane has a rather relevant role in the “Power-to-Gas” concept, which is central in the current paradigm of climate change and renewable energies. Methane, the main component of natural gas, can be produced by catalytic hydrogenation reactions, particularly of CO2. A very effective catalyst in this reaction, hydrotalcite-derived nickel nanoparticles supported on alumina, Ni/Al2O3-HTC, can be employed in a high-pressure flow reactor to convert CO2 and H2 into CH4 at 100% selectivity and 84% conversion, whereas at atmospheric pressure, methane can be obtained with up to 90% selectivity. The high-pressure aspect also allows fast-paced production—over 5 m3·h−1·kgcat−1 of CH4 can be generated.